Castro, Cuba, and the world - Gonzalez, Edward; Ronfeldt, David F.; Rand Corporation (Santa Monica, CA : RAND, 1986)
This report combines an analysis of Fidel Castro's mindset and patterns of behavior as a political actor with assessments of Cuba's current domestic and international situations, in order to assess Castro's foreign policy options through the late 1980s. The findings suggest that, in spite of signs of tactical moderation, Castro continues to adhere to the same maximalist ambitions and behavioral patterns that have characterized his rule for more than 25 years. He will work to ensure the survival of his Sandinista allies in Nicaragua and, if given Soviet backing, may actively seek to defeat the United States in southern Africa.
"June 1986."
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Castro, Fidel, -- 1927- -- Psychology; Heads of state -- Cuba -- Biography; Cuba -- Foreign relations -- 1959-; Cuba -- Politics and government -- 1959-